Pertumbuhan Tunas Tacca leontopetaloides L. Hasil Mikropropagasi Setelah Pemberian Radiasi Sinar Gamma Co60 dan Hormon Tumbuh yang Berbeda - Darnia Astari Parastiti; Endang Kusdiyantini; Endah Dwi Hastuti; Betalini Hapsari; Tri Muji Ermayanti (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2015)
Taca (Tacca leontopetaloides L.) is one of the plant family Dioscoreaceae that contain compounds glikosida flavonoid called taccalin and taccalonoides who potential as antioxidants. Taka (Tacca leontopetaloides L.) specifically has not been cultivated, grown only a limited area around the beach, it is necessary to plant vegetative propagation system faster with more results in tissue culture systems. This study aims to determine the growth and the antioxidant potential shoots Tacca leontopetaloides L. mikropropagasi results after administration of Co60 Gamma ray radiation and different growth hormones. Research method uses completely randomized factorial design (RAL) with 4 treatment doses of Gamma radiation Co60 is 0 Gy, 5 Gy, 20 Gy, and 30 Gy and 3 treatment of growth hormone that MSo, MSo + 0,5 BAP and MSo + 0,5 Kinetin with 3 replicates. Shoots taka from results mikropropagasi grown in vitro and has been irradiated with Co60 Gamma rays. Parameters tested were growth of shoots, amount of leaves, till, roots and wet weight taka. The results showed that Gamma radiation Co60 and plant regulator cytokinin effect on shoots taka, amount of tillers, leaf, root and wet weight taka. Keywords: Taka (Tacca leontopetaloides L.), Mikropropagation, Growth Hormone.